Dissecting the catalytic mechanism of Trypanosoma brucei trypanothione synthetase by kinetic analysis and computational modeling - Leroux, Alejandro E.; Haanstra, Jurgen R.; Bakker, Barbara M.; Krauth-Siegel, Renate (The journal of biological chemistry, 2013)
In pathogenic trypanosomes, trypanothione synthetase (TryS) catalyzes the synthesis of both glutathionylspermidine (Gsp) and trypanothione (bis(glutathionyl)spermidine (T(SH)2)). Here we present a thorough kinetic analysis of Trypanosoma brucei TryS in a newly developed phosphate buffer system at pH 7.0 and 37 °C, mimicking the physiological environment of the enzyme in the cytosol of bloodstream parasites. Under these conditions, TryS displays Km values for GSH, ATP, spermidine, and Gsp of 34, 18, 687, and 32 μm, respectively, as well as Ki values for GSH and T(SH)2 of 1 mm and 360 μm, respectively. As Gsp hydrolysis has a Km value of 5.6 mm, the in vivo amidase activity is probably negligible. To obtain deeper insight in the molecular mechanism of TryS, we have formulated alternative kinetic models, with elementary reaction steps represented by linear kinetic equations. The model parameters were fitted to the extensive matrix of steady-state data obtained for different substrate/product combinations under the in vivo-like conditions. The best model describes the full kinetic profile and is able to predict time course data that were not used for fitting. This system's biology approach to enzyme kinetics led us to conclude that (i) TryS follows a ter-reactant mechanism, (ii) the intermediate Gsp dissociates from the enzyme between the two catalytic steps, and (iii) T(SH)2 inhibits the enzyme by remaining bound at its product site and, as does the inhibitory GSH, by binding to the activated enzyme complex. The newly detected concerted substrate and product inhibition suggests that TryS activity is tightly regulated. Background: Trypanothione synthetase catalyzes the conjugation of spermidine with two GSH molecules to form trypanothione. Results: The kinetic parameters were measured under in vivo-like conditions. A mathematical model was developed describing the entire kinetic profile. Conclusion: Trypanothione synthetase is affected by substrate and product inhibition. Significance: The combined kinetic and modeling approaches provided a so far unprecedented insight in the mechanism of this parasite-specific enzyme.
Gesehen am 26.01.2022